Research on the Affecting Problems of Learning Strategies in Reading Comprehension - Yulia Nugrahini (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2018)
This paper presents the literature on reading comprehension and analyzes the influence of problems on students’ strategy use. Reading comprehension is one of the skill in English so the students must master that skill with the right strategies.The necessity of integrating social and individual problems in the studies of learning strategy, especially individual problems affecting the improvement of reading comprehension is made explicit, and this is followed by the description of situational problems and individual problems such as motivation, age, sex, and personality.